KORELASI BEBERAPA KOMPONEN KIMIA TERHADAP PENILAIAN ORGANOLEPTIK DAN HARGA BERAS BERMEREK YANG BEREDAR DI KOTA DENPASAR (STUDI KASUS DI PASAR SWALAYAN KOTA DENPASAR) - Wrasiati, Luh Putu; Hartiati, Amna; Ummy Indiyani, Ni Kadek (Agrotekno, 2014)
The  research  aimed to  (1)  observe  the  correlation  of chemical  component  rice  brand  with  organoleptik  of  yielded rice  test;  (2)  observe  the  correlation  of  chemical  components with  chosen  price  rice  brand;  (3)  determine  which  component have the most effect on organoleptik test of yielded rice.This  research  used  6  (six)  chosen  rice  brand  which were taken from supermarket that located in Denpasar by using purposive  sampling.  Analyses  covered  chemical  test  and organoleptik  test.  Chemical  test  cover  rate  test  of  amylase, amilopektin, and water content, the test of organoleptik covered test of scoring for texture, test hedonic to feel and acceptance of entirety.  The  result  of  organoleptik  test  was analyzed  with fragment  test  then  acceptance  mean  is  overall  was  test correlated  with  the  result  of  chemical  test  and  price  mean  of chosen rice.Result  of  acceptance  mean  of  organoleptik  overall data  indicate  that  rice  with  Bengawan  Super  brand  Sunflower was the most liked by consumers and brand C4 Super brand wasthe  least  taken  by  consumers.  Result  of  chemical  analysis indicate  that  the  water  rate  of  six  rice  brands  pursuant  to  SNI 01-6128-1999  and  rate  of  their  pertained  is  lower  until  mean. This results  indicated  that  the  regression  equation  between overall acceptance, with amylase rate and water rate (Y/X1/X3) was Y =  114,924  +  1,308 X1 - 0,037 X12 - 23,121 X3 +  1,105 X32 which  showed the  correlation  coefficient  was 0,760  and coefficient  of  determinacy  was 0,578.  This  correlation  hasshowed strong  level  relation.  Regression  equation  between chemical  component  and  the  price  of  brand  rice  have  chosen was Y  =  27791,960  - 13,810 X2 - 0,129 X22 - 3863,140 X3 + 175,691 X32 which showed the  correlation  coefficient  is  0,984 and coefficient of determination was 0,967. This correlation has very  strong  relation. Chemical  component which had the  most effect  to  the  texture was rate  of  amylase  and  amilopektin  with strong relation level. Chemical component which had the  most effect  on  rice  and  acceptance  of  entirety  rate  was  taste amilopektin level.
Keywords: rice, correlation among nutrition fact, sensory evaluation